The effect of polyamines and SICS on the compatibility, fertility and yield indices of apple cv. Golden Delicious - Pegah Sayyad-Amin; Gholamhossein Davarynejad; Bahram Abedy (Advances in Horticultural Science, 2018)
The most critical problems of temperate fruit trees are poor fruit set and low yield. To solve the problem, some major chemical compounds such as polyamines and SICS (self-incompatibility control substance, Mn+B) can be used. Popular polyamines including Putrescine (0.1 and 0.25 mM), both Spermine and Spermidine (0.05 and 0.25 mM), and SICS (1 and 2 mg L-1) were used alone or with cotton coverage bags to cover branches in order to investigate self-incompatibility in Malus domestica. Results showed that Spermidine (0.25 mM) led to higher yields in comparison with that of the control. SICS (2 mg L-1), also, demonstrated the highest yield compared with that of the control. At June fruit set, treatment with Spermidine (0.25 mM) led to the highest percentage of fruit set and also the highest index of self-incompatibility and percentage of final fruit set among treatments.